ANALISIS STRATEGI PENGEMBANGAN KAMPUNG PERIKANAN BUDIDAYA RUMPUT LAUT DI DESA LONTAR KABUPATEN SERANG - Iwang Gumilar; Haikal Dapa Heryadi; Asep Agus Handaka Suryana; Atikah Nurhayati (Universitas Mataram, 2024)
The amount of seaweed production in Lontar Village is decreasing every year so it is necessary to carry out an analysis to increase the amount of seaweed production in Lontar Village. In this research, a SWOT analysis was carried out for the direction of developing the seaweed cultivation business. Based on the results of the IFAS and EFAS analysis of internal and external factors, there are 5 factors. The strengths of the seaweed cultivation business in Lontar Village include community interest in large seaweed cultivation businesses, easy labor to obtain from family and community, seaweed cultivation equipment is simple and easy, large seaweed cultivation areas are available and harvest and maintenance periods can be arranged. Weaknesses in seaweed cultivation include lack of knowledge and skills in cultivation, seaweed is susceptible to pest and disease attacks, unsupportive quality and quantity of seeds, no seaweed processing industry and poor air quality which affects the harvest. Opportunities in the seaweed cultivation business include export market potential, superior products from government programs, the seaweed processing industry, seaweed cultivation technology as well as improving facilities and infrastructure. Threats from seaweed cultivation include the threat of climate change, the absence of training from extension workers, fluctuating seaweed prices, the loss of generations of seaweed cultivators and assistance from the government that is not yet in line with the farmers' needs and is not evenly distributed. The strategy that is suitable to be implemented is the S-O (Progressive) Strategy consisting of optimizing the cultivation area and the amount of seaweed production (S4, S5, O1, O2), the use of technology in seaweed cultivation accompanied by training (S1, S3, O4, O5) and training. and HACCP certification for cultivators (S1, O1, O2).